Reactivity Factors in Catalytic Methanogenesis and Their Tuning upon Coenzyme F430 Biosynthesis - Bharadwaz, Priyam; Maldonado-Domínguez, Mauricio; Chalupský, Jakub; Srnec, Martin (Journal of the American Chemical Society, 2023)
Methyl-coenzyme M reductase, responsible for the biological production of methane by catalyzing the reaction between coenzymes B (CoBS-H) and M (H3C-SCoM), hosts in its core an F430 cofactor with the low-valent NiI ion. The critical methanogenic step involves F430-assisted reductive cleavage of the H3C-S bond in coenzyme M, yielding the transient CH3 radical capable of hydrogen atom abstraction from the S-H bond in coenzyme B. Here, we computationally explored whether and why F430 is unique for methanogenesis in comparison to four identified precursors formed consecutively during its biosynthesis. Indeed, all precursors are less proficient than the native F430, and catalytic competence improves at each biosynthetic step toward F430. Against the expectation that F430 is tuned to be the strongest possible reductant to expedite the rate-determining reductive cleavage of H3C-S by NiI, we discovered the opposite. The unfavorable increase in reduction potential along the F430 biosynthetic pathway is outweighed by strengthening of the Ni-S bond formed upon reductive cleavage of the H3C-S bond. We found that F430 is the weakest electron donor, compared to its precursors, giving rise to the most covalent Ni-S bond, which stabilizes the transition state and hence reduces the rate-determining barrier. In addition, the transition state displays high pro-reactive motion of the transient CH3 fragment toward the H-S bond, superior to its biosynthetic ancestors and likely preventing the formation of a deleterious radical intermediate. Thus, we show a plausible view of how the evolutionary driving force shaped the biocatalytic proficiency of F430 toward CH4 formation.
Keywords: metaloporfyriny; Methane; katalýza; oxidace-redukce; Catalysis; Metalloporphyrins; Oxidation-Reduction; biokatalýza; Biocatalysis; methan